The Relationship Between The Body Mass Index and The Pain Threshold in Myofascial Pain Syndrome: A Cross-sectional Study - Ibrahim Agung; Nyoman Murdana; Herdiman Purba (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Introduction: The obesity on the myofascial pain syndrome (MPS) was reduced the pain thresholds, leads todecreasing of physical functioning and quality of life. The obese group was more sensitive to pain due to the proinflammatorycondition. This study aimed to examined the relationship between the Body Mass Index (BMI)and the pain threshold in MPS patients.Methods and Materials: This study was a cross-sectional study, conducted in an outpatient clinic of MedicalRehabilitation Department of Dr. Cipto Mangunkusumo Hospital, Jakarta. The subjects recruited consecutively.The pain intensity was assessed subjectively by the Visual Analogue Scale (VAS) score from 0 to 10. Thenumber of the trigger points (TP) were examined palpation manually. The pain threshold was evaluated by thealgometer (Kg) on the upper trapezius muscles.Results: The study has recruited 30 patients, aged 40,5 (20-54). The BMI was 24.97 ± 3.39 Kg/M2. The VASscore was 6 (5-8). The number of the TP was 5.83 ± 1.74. The pain threshold was 2.48 ± 0.52 Kg/ cm2. Most ofthe subjects have overweight (20%) and obesity (47%). There was no correlation between the BMI with the painintensity (r=-0.076, p=0.689), with the number of trigger points (r=0.256, p=0.171) and with the pain threshold(r=0.189, p=0.316).Conclusions: Therefore the BMI was not related to the pain intensity, the number of trigger points as wellas with the threshold of pain in the MPS patients. However, the number of the TP tends to increase, and thethreshold of pain has the tendency to reduced in the obese subjects.Keywords: Obesity; Myofascial Pain Syndrome; VAS; Pain Threshold